Bose-Einstein condensation from a gluon transport equation - Harrison, Brent (Department of Physics, 2019)
In this thesis we investigate the evolution of the quark gluon plasma, as produced in the early stages of a relativistic heavy ion collision, towards equilibrium. To this end we put forward a new numerical scheme to solve the QCD Boltzmann equation in the small-scattering angle approximation, which we develop here for the quenched limit of QCD. We initially restrict our analysis to spatially homogeneous systems of gluons distributed isotropically in momentum space. With our scheme we confirm results of Blaizot et al. [1], in particular that for certain “overpopulated” initial conditions, a transient Bose-Einstein condensate emerges during equilibriation in a finite time. We further analyse the dynamics of the formation of this condensate. We then extend our scheme to systems with cylindrically symmetric momentum distributions, in order to investigate the effects of anisotropy. In particular we compare the rates at which isotropization and equilibriation occur. We also compare our results from the small-scattering angle scheme to the relaxation-time approximation.